War No More : The Antiwar Impulse in American Literature, 1861-1914 - Wachtell, Cynthia, 1967- (Book collections on Project MUSE., 2010)
Until now, scholars have portrayed AmericaAEs antiwar literature as an outgrowth of World War I, manifested in the works of writers such as Ernest Hemingway and John Dos Passos. But in War No More, Cynthia Wachtell corrects the record by tracing the steady and inexorable rise of antiwar writing in American literature from the Civil War to the eve of World War I. Beginning with an examination of three very different renderings of the chaotic Battle of Chickamaugaùa diary entry by a northern infantry officer, a poem romanticizing war authored by a young southerner a few months later, and a grueso.